Tourism Potential and Assessment of the Mount Bazarduzu - Mustafayeva Gulnisa; Allahverdiyeva Muslumat; Alizada Narmin; Urinbaev Sh. (BIO Web of Conferences)
Mountain tourism, one of the main tourism resources in the world, is developing rapidly. Despite the presence of many mountains worthy of evaluation in this field, the tourism sector is underdeveloped. Mount Bazarduzu, especially known for its 4466 meters high and outstanding appearance, is among the mountains with significant tourism potential in our country. However, despite this potential of Mount Bazarduzu, its underutilization is due to certain obstacles. When examining the reasons why the tourism potential of Mount Bazarduzu is not fully utilized, we encounter problems such as bureaucratic obstacles, insufficient promotion, lack of qualified personnel in this sector, lack of recognition as a destination, inadequate local and regional transportation infrastructure, lack of museums, limited accommodation options and lack of government incentives for tourism professionals. In addition, the lack of a comprehensive and unified marketing strategy, weak interest of the local population in tourism and insufficient promotion of the tourist resources of Mount Bazarduzu and its surroundings in the international tourism arena are serious problems. The purpose of this study is to draw attention to the tourist potential and possibilities of using the mountainous areas of our country, especially Mount Bazarduzu, in the context of geography and tourism, identify existing problems, prepare proposals for their solution and raise awareness on this topic.